A review of educational games design frameworks: An analysis from software engineering - Ahmad, M. (Institute of Electrical and Electronics Engineers Inc., 2014)
Game-based learning allows leveraging on young learners preference towards playing games to turn games into tools for learning. There are a number of frameworks developed in the various aspects and theories of game-based learning. There are many relationships in existing frameworks that has been discussed regarding certain domains such as subject-matter expert, the game environment, developers, game goals and game designs, however, the relationship between subject-matter, game environment, learning theories and game-play is yet to be discussed together. This paper analyzes a few educational frameworks and discusses their relations among domains that they have used. In addition, this paper will discuss the software engineering practices that is of concern to educational games development but have not been discussed in previous literature. Â© 2014 IEEE.